Análisis de la dinámica estelar en el marco de la teoría de Rastall - Rivas Ramírez, Juan José (Universidad Michoacana de San Nicolás de Hidalgo, 2020)
In the context of the Rastall theory of gravitation for a static spherically symmetric geometry, imposing the invariance of the system of the ordinary differential equations associated with stellar models, we show that the equation of state that is consistent with this condition is P = (γ - 1)c2p, where P is the pressure, p is the density, c is the speed of light, and γ is the parameter of state. This mathematical result coincides with one of the formulated equations of state draw from the physical conditions for which γ ϵ (1, 2). With this equation of state, we present the analysis of the dynamic system, showing that the following exist: two equilibrium points, one saddle point, and one spiral point. The last one corresponds to a generalization of the Misner- Zapolsky solution, which depends on the parameter of state γ and the Rastall parameter λ. We additionally show that, for λ ϵ [0, 1] and λ(1, 2), there are regions where the conditions of null (NEC), weak (WEC), strong (SEC), and dominant (DEC) energy conditions, along with the existence of stable solutions (spirals), cannot be found simultaneously.

En el marco de teoría de gravitación de Rastall para una geometría estática y esféricamente simétrica, imponiendo la invarianza del sistema de ecuaciones diferenciales ordinarias asociadas a modelos estelares, mostramos que la ecuación de estado consistente con esta condición es P = (γ - 1)c2p, donde P es la presión, p es la densidad, c es la velocidad de la luz y γ es el parámetro de estado. Este resultado matemático coincide con una de las ecuaciones de estado formuladas a partir de condiciones físicas para el que γ ϵ (1,2) sistema dinámico, mostrando que existen dos puntos de equilibrio; un punto silla y un punto espiral, este último corresponde a una generalización de la solución de Misner-Zapolsky, que depende del parámetro de estado y el parámetro de Rastall γ. De manera complementaria mostramos que para λ ϵ [0, 1] y (1; 2) existen regiones donde las condiciones de energías: Nula (NEC), Débil (WEC), Fuerte (SEC), Dominante (DEC), y la existencia de soluciones estables (espirales) no se tienen simultáneamente.
Facultad de Ciencias Físico Matemáticas. Maestría en Ciencias en Ingeniería Física
Keywords: info:eu-repo/classification/cti/1; FISMAT-M-2020-1110; Cuasi-homología; Rastall; Frobenius; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3315